Perancangan Aplikasi FinTech Locavest sebagai Sistem Pendukung Keputusan Analisis Kelayakan Lokasi Usaha Menggunakan Metode Design Thinking - Muhamad Ikhsan Tazudin; Randhu Fulki Ramadhan; Hyuga Ramdhan Noer; Genta Nazwar Tarempa (Jurnal Teknologi Informasi dan Multimedia, 2026)
The development of financial technology (fintech) and artificial intelligence (AI) opens up oppor-tunities to increase efficiency and objectivity in business decision-making, including business loca-tion selection. However, the integration of fintech, property, and AI-based location analysis in a single mobile platform has rarely been comprehensively studied. This study designed a prototype of the Locavest application as an AI-based fintech solution for business location feasibility analy-sis using a Design Thinking approach. The development method included the stages of empathize, define, ideate, prototype, and test to ensure the suitability of the features to the needs of MSMEs and novice investors. Prototype validation was conducted using the System Usability Scale (SUS) with 10 user respondents, resulting in an average score of 85, indicating a very good level of usability (category "excellent"). This application is expected to become an integrated decision support sys-tem that can help users analyze business locations and property investments more quickly, meas-urably, and easily. The contribution of this research lies in the integration of fintech, property, and AI features in a single mobile application and the use of Design Thinking methods to produce in-novative and user-friendly digital solutions.